TRIGLYCERIDES AND CHOLESTEROL SERUM LEVELS IN PERUVIAN PASO HORSES UNDER TWO REARING SYSTEMS - Díaz C., César (2008)
The objective of the study was to compare the level of triglycerides (TG), totalcholesterol (TC) and its fractions (VLDC-C, LDL-C and HDL-C) in blood serum of PeruvianPaso Horses (CPP) in the Lambayeque Region. Serum of 50 CPP animals (25 sedentaryand 25 active) were analyzed. TG and TC levels were determined using commercial kits,whereas HDL-C and LDL-C were determined using selective polymer precipitants (dextransulphate, Mg++). VLDL-C was calculated by subtracting HDL-C + LDL-C values from TClevels. Mean values were 25.69 mg/dl for TG, 108.71 mg/dl for TC, 66.55 mg/dl for HDL-C,21.38 mg/dl for LDL-C, and 20.78 mg/dl for VLDL-C. HDL-C serum values in active CPPanimals were statistically higher than in sedentary horses (p<0.01), whereas TG values were statistically lower in castrated horses as compared to mares (p<0.05). Sedentary horses registered lower levels of HDL-C as compared with active animals, but the latter have lesser atherogenic risk; however, both active and sedentary horses have low susceptibility to get hypertrigliceridemia.